A study on the implementation of remote learning: Malaysian students’ struggles and suggestions for improvement - Muhammad Noor Abdul Aziz; Nurliyana Bukhari; Nurahimah Mohd Yusoff; Yusnidah Ibrahim; Abdul Malek Abdul Karim; Mohd Isha Awang; Aspalila Shapii (Institute of Advanced Engineering and Science, 2023)
This study seeks to explore Malaysian undergraduates’ perspectives on the implementation of remote learning in their university during the period of the movement control order (MCO). Since teaching and learning activities have been impacted by the pandemic, it is imperative to consider students’ perspectives on carrying out classes via the online platform as many studies claim that the pandemic has disrupted teaching and learning activities. A total of 1,028 undergraduate students participated in this voluntary study by answering an open-ended survey sent out to their student email addresses during the MCO period that restricted students and lecturers from going to the university. The qualitative responses from the students were critically analyzed for thematic patterns. The four themes emerging from the data provide future teaching and learning plans that should embed self-learning techniques that could aid students if a similar predicament should hit us in the future. Course instructors can use this information to design future lessons that could assist their learners better.